1994
DOI: 10.1093/fampra/11.3.296
|View full text |Cite
|
Sign up to set email alerts
|

Is the Potential of Teenage Consultations Being Missed?: a Study of Consultation Times in Primary Care

Abstract: There is a paucity of knowledge regarding teenage health even though it features as one of the priority areas in the government's health plans. There have been few reports of adolescent contacts with primary care teams, although there are impressions of a suboptimal service. As a prelude to understanding more about communication between general practitioners and teenage patients, this study aimed to look at the time spent on teenage consultations, which can be used as one method of describing the quality of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 0 publications
0
28
0
2
Order By: Relevance
“…3 Previous studies have also showed consultations with teenagers are shorter than for other age groups. 10 In 2009, adolescents accounted for 18% of the world population, with a majority of them (88%) lived in developing countries. 10 India's Adolescents population is 253 million (22% of total population) and highest in the world.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…3 Previous studies have also showed consultations with teenagers are shorter than for other age groups. 10 In 2009, adolescents accounted for 18% of the world population, with a majority of them (88%) lived in developing countries. 10 India's Adolescents population is 253 million (22% of total population) and highest in the world.…”
Section: Discussionmentioning
confidence: 99%
“…10 In 2009, adolescents accounted for 18% of the world population, with a majority of them (88%) lived in developing countries. 10 India's Adolescents population is 253 million (22% of total population) and highest in the world. Studies show that investing in the health of adolescents prevents the estimated 1.4 million deaths that occur globally every year.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, studies have reported that a familiar trusted person can improve communication and adolescents are more willing to discuss topics that have been previously discussed [31]. Time available for consultation is an important parameter of increased quality in health care of adolescents, as has been consistently shown [23,24,27,32,33]. Confidentiality and privacy have been also shown to be critical for high quality health care for adolescents and research has shown that adolescents who forgo health care due to confidentiality concerns are particularly vulnerable and in need of health services [34,35].…”
Section: Discussionmentioning
confidence: 99%